Overexpression of amyloid precursor protein inhibits neurite outgrowth and disrupts cytoskeleton in N2a cells - 王泽芬 王建枝 (Chinese medical journal, 2004)
There is considerable evidence suggesting that altered metabolism of β-amyloid precursor protein (APP) and accumulation of its β-amyloid (Aβ) fragment are key features of Alzheimer' s disease (AD). APP is a type Ⅰ integral membrane protein and consists of 695 - 770 amino acids encoded by differentially spliced mRNAs transcribed from a single gene located on human chromosome 21. The 695-amino acid APP is expressed preferentially in the brain. Aβ, the major component of senile plaques, is derived by proteolytic processing of APP by β-and γ-secretase and is constitutively released from most cells.